ASSESSMENT OF INTERPOLATION METHODS IN DATA RAINFALL AND THE SPATIAL DISTRIBUTION - RODRIGUES, Mikael T.; RODRIGUES, Bruno T.; MONTE, Benicio E. O. (Revista Brasileira de Engenharia de Biossistemas, 2012)
The objective is to compare two (2) univariate interpolation, inverse distance squared - IDW and kriging using precipitation data provided by WRF run covering the entire basin of the Rio Paraiba do Meio and evaluate the performance of interpolators for the period 2008 and January, February and March 2009. The maps did not show large spatial variability in visual spatial differences, however, the IDW was less detailed, using inverse distance weighted interpolation and determines cell values ​​using a weighted linear combination of a set of sampling points, stating as great technique for spatial rainfall totals.